Alienation amongst black students at a predominantly white university - Leon, Natalie; Lea, Susan (PINS-Psychology in Society, 2025)
In South Africa today there are twenty-one universities. Like so many other aspects of existence in South Africa, universities are broadly segregated along racial lines. Certain universities are regarded as "open" universities - in effect these are mainly white English-speaking universities which accept some black students, but these remain very much in the minority. At UCT black students make up 20% of the university student body (van der Merwe, 1987). This situation raises questions about how black students adjust to attending a white majority campus.